Digital Consumer Protection: A Comparative Analysis of Exploitative Game Monetization in Indonesia and The Netherlands - Rifansyah Nugraha; Diani Sadiawati (Fakultas Syariah INSURI Ponorogo, 2026)
Rapid technological advancements have prompted online game companies to implement monetization in their games to generate revenue; games that employ monetization are typically found in the gacha genre. The implementation of monetization is a cause for concern because such monetization schemes may constitute unfair or exploitative practices that are not yet adequately regulated under Indonesian law. This study aims to examine a comparative analysis of legal protections for consumers against monetization in gacha games by gaming companies in Indonesia and the Netherlands, and to propose regulatory solutions that the government can implement to address the legal vacuum surrounding such monetization practices in Indonesia. This study employs a normative legal methodology using a legislative approach. The data utilized are sourced from primary, secondary, and tertiary legal materials. The results of the study indicate that Indonesia has not yet specifically regulated the characteristics of probability-based gacha monetization systems. This situation creates a regulatory gap in digital consumer protection. The effectiveness of consumer protection can be enhanced by integrating a modern, digital-risk-based framework, supported by a dedicated regulatory body to enforce it.